Haemato‐biochemistry, erythromorphology, and histopathology of Oreochromis niloticus as influenced by Aeromonas hydrophila infection and florfenicol therapy - Joshi Sharon; Thangapalam Jawahar Abraham; Arya Sen; Ratnapriya Das; Priyanka Sinha; Satyanarayana Boda; Prasanna Kumar Patil (Animal Research and One Health)
Abstract Aeromonas hydrophila infection is one of the key factors limiting tilapia production, and antibiotics play important roles in the control of diseases. This study evaluated the effectiveness of florfenicol (FFC) when administered orally at the therapeutic dose of 15 mg/kg fish biomass/day for 10 days against A. hydrophila infection in Oreochromis niloticus in terms of survival, changes in haemato‐biochemistry, erythrocyte morphology, and histoarchitecture of the vital organs. A. hydrophila was moderately virulent to tilapia with an LD50 of 1.15 × 107 cells/fish. When challenged, it caused systemic infection in fish. The challenged fish were lethargic, wandered around the corners, rested at the bottom, swam vertically, and darkly pigmented. The FFC therapy effectively reduced bacteria‐induced mortalities and physiological stress as the measured haemato‐biochemical parameters indicated. The histopathological findings suggested alterations in tissue architecture of the kidney and liver tissues, which improved in the treated fish. Erythrocytes of the challenged fish showed elongated, irregular‐shaped, tear‐drop‐shaped, crenated, and hypochromic erythrocytes, ragged cytoplasmic membranes, vacuolation, hypertrophied nucleus, and eccentric nucleus. These morphological alterations were reduced with FFC therapy. Compared to the untreated group, the FFC treatment normalized the haemato‐biochemical parameters, improved wound healing, and promoted fish recovery against bacterial infections. The results hinted at the effectiveness of FFC against A. hydrophila infection in O. niloticus juveniles at the therapeutic dose. However, care must be taken for its judicious aquacultural application to avoid its negative impacts on fish, the environment, and consumers.